(untitled) - Yong, T. (Rome, 1992)
The notion of sustainability has been developing for some time in both economics and ecology literature. Much of the economics of renewable resource has been concerned with sustainable yields,...
Keywords: Sustainable agriculture,Natural resources,Agriculture and state,Nông nghiệp bền vững